Production and properties of metal-bonded La(Fe, Mn, Si)13Hx composite material. (1st April 2017) - Radulov, I.A.; Karpenkov, D. Yu.; Skokov, K.P.; Karpenkov, A. Yu.; Braun, T.; Brabänder, V.; Gottschall, T.; Pabst, M.; Stoll, B.; Gutfleisch, O.
Abstract: Due to their excellent magnetocaloric properties hydrogenated La(Fe, Mn, Si)13 are considered as promising and cost efficient materials for active magnetic regenerators operating near room temperature. However, due to their poor mechanical and chemical stability this alloys can not be directly implemented in a cooling machine. A solution of the problem is the production of a composite La(Fe, Mn, Si)13 H x magnetocaloric materials by using adhesive-bonding techniques similar to those used for production of polymer-bonded permanent magnets. Upon bonding one has to consider that the thermal stability of the polymer binder is rather low. Main disadvantage of a polymer-bonded composite is the fatigue due to the mechanical stress caused by the large magnetovolume effect in La(Fe, Mn, Si)13 H x . Our article reports on a new method and equipment to produce metal-bonded magnetocaloric material using the low melting eutectic Field's alloy as a binder. A comprehensive investigation of the magnetocaloric, mechanical, chemical and thermal transport properties of polymer-bonded and metal-bonded magnetocaloric material is presented. Graphical abstract: Image 1